Influence of PV/T waste heat on water productivity and electricity generation of solar stills using heat pipes and thermoelectric generator: An experimental study and environmental analysis. (15th January 2023) - Shoeibi, Shahin; Saemian, Mohammad; Khiadani, Mehdi; Kargarsharifabad, Hadi; Ali Agha Mirjalily, Seyed
Highlights: The combination of PV and solar still using heat pipe and TEG was assessed. Energy, exergy and electrical efficiencies of the system was improved. Water and electrical generation of the SS-HP-WT was increase by 55.3% and 20.9%. CPL and CPP of the SS-HP-WT were about 0.042 /L and 0.061 /kWh. Abstract: In recent years, numerous studies have been performed to improve the evaporation rate of solar stills and the electrical power of the photovoltaic module. In this paper, an experimental study of modified single slope solar still integrated with a photovoltaic panel, heat pipes and thermoelectric generator to enhance the performance of solar still is presented and compared with conventional solar stills. Five heat pipes were proposed and installed below a photovoltaic module to transfer the generated waste heat to the saline water of a solar still. Two thermoelectric generators were installed between the photovoltaic panel (hot sides) and the cooling water block (cold sides) to use the generated waste heat. The saline water flows to the cooling water block and then to the evaporation zones of the heat pipes to increase the water temperature and enhance the electrical power of the photovoltaic panel and thermoelectric generator. Results showed that the highest hourly power generation of the solar panel of conventional solar still (CSS), solar still by water cooling and thermoelectric generators (SS-WT), solar still by heat pipes (SS-HP) and solar still by heat pipes, water cooling and thermoelectric generators (SS-HP-WT) was about 68 W, 69 W, 73 W and 75 W, respectively. Also, the daily water productivity of CSS, SS-WT, SS-HP and SS-HP-WT was about 748 ml/m 2, 832 ml/m 2, 1058 ml/m 2 and 1162 ml/m 2, respectively. Moreover, CPL of CSS, SS-WT, SS-HP and SS-HP-WT were about 0.042 /L, 0.098 /L, 0.077 /L, 0.084 /L, respectively. In addition, cost per power production of conventional photovoltaic, SS-WT, SS-HP and SS-HP-WT were about 0.061 /kWh, 0.141 /kWh, 0.128 /kWh and 0.147/kWh, respectively.